Risk, burden and control of non-polio enterovirus infections - Cai, E (2020)
Non-polio enteroviruses are a large and diverse group of viruses that cause a wide spectrum of disease syndromes, ranging from mild, self-limiting cutaneous infections (hand-foot-mouth disease or herpangina), through to serious neurological complications such as encephalitis and life-threatening pulmonary haemorrhage or fulminant myocarditis. The international health risk posed by these viruses is demonstrated by the ongoing burden of enterovirus A71 in southeast and east Asia since its re-emergence in 1997, and the more recent re-emergence of enterovirus D68 in Europe and North America associated with severe respiratory disease and acute flaccid paralysis.